Picturing American modernity : traffic, technology, and the silent cinema - Whissel, Kristen, 1969- (Duke backfile, 2008)
In Picturing American Modernity, Kristen Whissel investigates the relationship between early American cinema and the experience of technological modernity. She demonstrates how between the late 1890s and the eve of the First World War moving pictures helped the U.S. public understand the possibilities and perils of new forms of "traffic" produced by industrialization and urbanization. As more efficient ways to move people, goods, and information transformed work and leisure at home and contributed to the expansion of the U.S. empire abroad, silent films presented compelling visual representations of the spaces, bodies, machines, and forms of mobility that increasingly defined modern life in the United States and its new territories. Whissel shows that by portraying key events, achievements, and anxieties, the cinema invited American audiences to participate in the rapidly changing world around them. Moving pictures provided astonishing visual dispatches from military camps prior to the outbreak of fighting in the Spanish-American War. They allowed audiences to delight in images of the Pan-American Exposition, and also to mourn the assassination of President McKinley there. One early film genre, the reenactment, presented spectators with renditions of bloody battles fought overseas during the Philippine-American War. Early features offered sensational dramatizations of the scandalous "white slave trade," which was often linked to immigration and new forms of urban work and leisure. By bringing these frequently distant events and anxieties "near" to audiences in cities and towns across the country, the cinema helped construct an American national identity for the machine age